Validity and reliability of the 12-item Berg Balance Scale in an Italian population with Parkinson’s disease: A cross sectional study - BERARDI, Anna; GALEOTO, Giovanni; VALENTE, Donatella; CONTE, Antonella; FABBRINI, Giovanni; TOFANI, Marco (Arquivos de Neuro-Psiquiatria, 2020)
Background: The Berg Balance Scale is widely used to measure balance ability in clinical practice. Recently, the original version was redefined from 14 into 12 items. Its psychometric properties were investigated for different populations. However, for Parkinson disease the new version has not been validated yet. Objective: The purpose of the present study was to evaluate psychometric properties of the 12-item Berg Balance Scale (BBS-12) in a population with Parkinson disease. Methods: Internal consistency was evaluated with Cronbach’s alpha coefficient, whereas reliability was assessed with the intraclass correlation coefficient. For validity analysis, the Pearson correlation coefficient of the BBS-12 was evaluated with the Tinetti Scale and the Physical Activity Scale for the Elderly. Results: The BBS-12 was applied to 50 individuals with a mean age of 65.6 years (SD 11.8). The internal consistency showed a good value (Cronbach's alpha 0.886) and reproducibility reveled very high performances for both inter-rater and intra-rater reliabilities (ICC 0.987 and 0.986, respectively). The validity study demonstrated good linear correlation with the Tinetti Scale (p<0.01) and with the Sport and Home Subscales of the Physical Activity Scale for the Elderly (p<0.01). Conclusions: The present findings revealed the BBS-12 as a reliable and valid assessment tool to measure balance ability in Parkinson disease. Italian health professionals can now use it with more confidence.
Keywords: Parkinson Disease; Postural Balance; Psychometrics; Validation Studies; Outcome Measure